Uji Aktivitas Antimikroba dan Uji Sitotoksik Ekstrak Etanol Akar Tanaman Akar Kucing (Acalypha indica Linn), Daging Buah Mahkota Dewa (Phaleria macrocarpa (Sheff) Boerl) dan Sari Buah Merah (Pandanus conoideus Lam) - Radji, Maksum; Sari, Ratna Chandra; Sumiati, Atiek (Majalah Ilmu Kefarmasian, 2008)
The antimicrobial activity and cytotoxic effect of ethanol extract of Acalypha indica Linn, Phaleria macrocarpa (Sheff) Boerl and Pandanus conoideus Lam, had been carried out. The results of the research showed that those ethanol extracts had antimi-crobial activities against Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, Pseudomonas aeruginosae ATCC 27853 and Candida albicans. The determi-nation of cytotoxic effects of those ethanol extracts by brine shrimp lethality test (BSLT) using Artemia salina Leach showed that LC50 of Acalypha indica Linn, Phaleria macrocarpa (Sheff) Boerl and Pandanus conoideus Lam were 1,279 ug/ml, 0.123 ug/ml and 0.054 ug/ml respectively.